Photocatalytic Degradation Activity of the Biosynthesized R. rosifolius Mediated Silver Nanoparticles in Methylene Blue Dye - Martin, Marilen M.; Sumayao, Jr., Rodolfo E.; Soriano, Allan N.; Rubi, Rugi Vicente C. (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
Water pollution is a chronic problem affecting the entire ecosystem. To partly remediate water pollution, wastewater treatment prior to disposal must be done regularly. Here, the photocatalytic degradation of methylene blue (MB) dye was assessed using R. rosifolius Linn (also known as sampinit) aqueous fruit extract silver nanoparticles (SAFE-AgNPs). In this study, the SAFE-AgNPs were utilized to remediate wastewater contaminated with methylene blue (MB) dye which is harmful to the environment, aquatic and human lives. As previously described, SAFE-AgNPs were synthesized via a simple ‘one-pot’ approach. SAFE-AgNPs were assessed for their photocatalytic reduction of MB dye following sunlight or LED irradiation. Kinetic adsorption models were employed to determine the adsorption uptake of MB by SAFE-AgNPs. Photocatalytic degradation of methylene blue by SAFE-AgNPs was achieved under sunlight and LED irradiations at 98.8% and 97.6%, respectively. These results on the photocatalytic degradation of MB by SAFE-AgNPs may offer a potential strategy in wastewater treatment.